Small hydro-power plant project selection using fuzzy axiomatic design principles - Khandekar, Anant V.; Antuchevičienė, Jurgita; Chakraborty, Shankar (Technological and Economic Development of Economy, 2015)
There has been a rapid growth in construction activities during the last few decades owing to overall development in all facets of humanity. Due to technological advancements and ever increasing civilization, there is a persistent need of energy. Along with the conventional energy sources, the renewable energy sources have also significantly contributed to the rising energy needs. As a renewable source of energy, numerous small hydro-power plants (SHPPs) have been built up across the world in the recent past. Usually these SHPPs are being built and operated by the private developers complying with the government regulations. In order to assist a developer in selecting the most profitable and feasible SHPP for construction and subsequent operation, a method based on fuzzy axiomatic design principles is employed in this paper. The techno-commercial and socioeconomic criteria as considered for analyzing the feasibility of the candidate SHPPs are expressed qualitatively using trapezoidal fuzzy numbers. The performance of each SHPP is evaluated in terms of its total information content and the one with the least information content is selected to be the best venture for the required construction activity. The adopted methodology is found to have immense potential to the developers while selecting the most feasible project for construction.